THE UTILIZATION OF GOLDEN PERIOD OF ISCHEMIC STROKE IN PATIENTS IN PRODUCTIVE AGES - Vidya Tri Huttami; Atik Choirul Hidajah (The Indonesian Journal of Public Health, 2020)
The 2007 Basic Health Survey shows the highest number of deaths in Indonesia rural and urban areas was caused by stroke. In 2007-2013, the stroke prevalence in  productive age increased up to 22‰. Stroke that attacks productive age can impair individual’s ability to do activities, and thus they might have family financial constraint. Disabilities can be prevented and minimized if patients utilize a golden period of an ischemic stroke. This study identified the utilization of golden period of ischemic stroke in patients and analyzed causes of delayed patient admission to the Neurology Clinic of Sidoarjo Hospital. This study was a descriptive study conducted to 39 post-stroke ischemic patients in productive ages under further therapy at the Neurology Clinic of Sidoarjo Hospital in 2016. The data were collected through interview from January-February 2017. The results present 62% of stroke ischemic patients utilized the golden period of a ischemic stroke. The average respondents' admission took  29.87±47.46 hours after patients experienced first stroke ischemic attacks (ranging from 1-168 hours). The respondents were admitted to the hospital late or >4.5 hours after the stroke attacks because most of them did not know stroke signs and symptoms. Therefore, hospitals or health care providers have to provide counseling service to patients and family members about stroke signs and symptoms, as well as the importance of early admission for treatment as soon as patient gets the first stroke attack. Keywords: utilization of the golden period, ischemic stroke, productive age.